Quantifying interfacial substrate interactions via surface energy analyses - T. Brian Cavitt; Jasmine G. Carlisle; Rachel A. Brooks; Lauren G. Scott; Pooja R. Patel (STAR Protocols, 2021)
Summary: Determination of a substrate’s surface energy profile is a facile and inexpensive method to indicate the substrate’s interfacial thermodynamics with another substance (e.g., microorganisms, biomacromolecules, medical devices, etc). The following protocol details a goniometric method to calculate a substrate’s surface energy profile which (1) directly correlates to a substrate’s interfacial Gibbs energy (ΔG) and (2) predicts the interfacial interactions with other substances. We also provide a calculation template using advanced mathematics to expedite surface energy profile determination.For complete details on the use and execution of this protocol, please refer to Cavitt et al. (2020).